Modified Kapok Fibers (Ceiba pentandra (L.) Gaerth) for Oil Spill Remediation - Oliveira, Leonardo M. T. M.; Fonseca, Eduardo J. S.; Bernardo, Vanderson B.; Zanta, Carmem L. P. S.; Oliveira, Laís F. A. M.; Oliveira, Jennifer N. S. R. de; Souza, Samuel T. de; Duarte, José Leandro da Silva (Applied sciences, 2024)
The search for efficient oil spill remediation techniques leads to the use of physical, chemical, and biological methods, featuring both natural and modified lipophilic materials. Kapok fibers (Ceiba pentandra (L.) Gaerth) have been studied as a result of their unusual natural oil sorption capacity, which can be improved even further through physical or chemical treatments that augment their rugosity and alter their functional properties. Furthermore, the exact role of fiber morphology is not completely clear regarding the sorption process. Hence, this study investigated the efficacy of kapok fibers using different treatments, based on chemical and physical approaches, and characterized using advanced techniques (FTIR, SEM, AFM), aiming to improve the understanding of application possibilities in oil contamination scenarios. The results indicate that treatments using a low thermal intensity and low concentration do not lead to variation in sorption properties nor in surface structural features. Fiber rugosity varied from 4.40 to 12.35 nm, whereas an excessive increase in roughness was observed when the material was subject to more extreme conditions, such as a temperature of 120 °C and high concentrations (2.0 M) of both acid or alkali, accompanied by a loss in functionality and affecting the material sorption capacity. Thus, the study provides conditions to suggest that these treatments are not necessary for this type of material when inserted into sorption processes.